Analysis of subsurface layer formation on a pearlitic rail under heavy haul conditions: Spalling characterization. (December 2021) - Pereira, J.I.; Tressia, G.; Kina, E.J.; Sinatora, A.; Souza, R.M.
Highlights: The combination of rolling/sliding contact and wheel brake promote a large microstructural transformation in the sub-surface. The WEL consisted in martensite due a thermally-induced transformation. The gradual decrease of hardness is suggesting the combination of metallurgical phases in the transitional layer. The spalling is promoted by the change of crack propagation in the transitional layer. Abstract: The depth of rolling contact fatigue (RCF) defects in railways plays a significant role in the rail lifetime, affecting rail maintenance procedures due to the amount of material to be removed from the railhead. Therefore, a precise characterization of the damaged rail is needed to define the optimal material removal. In the present study, an ex-service and damaged rail that contained defects due to RCF was investigated in detail. The microstructural characterization was conducted on particular sites using optical microscopy (OM), scanning electron microscopy (SEM), SEM with focused ion beam (SEM-FIB), electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). Three layers were identified at the rail cross section: a white etching layer (WEL) was the topmost layer and comprised martensite; a transitional layer (TL) with martensite and retained austenite was identified below the WEL; followed by a severely plastically deformed layer with refined grains and a large number of high-angle boundaries (HABs) and elongated pearlite colonies. In this last region, {1 1 1} and {1 1 0} were common crystallographic orientations. A gradual decrease in the hardness was observed along these layers. The WEL achieved a hardness value of 12 GPa, while the TL had an average value of 8 GPa, and measurements on the plastically deformed layer indicated a hardness of 6 GPa. The observed microstructural transformation suggests that thermal loading led to a thermally produced WEL (TP-WEL). The brittle nature of the WEL and the surface shear deformation and high levels of stress promoted the nucleation of surface cracks and propagation of them through the WEL. The presence of the different metallurgical phases in the TL promoted a change of crack orientation, leading to material detachment.